Degradable porous nanoflower substrate-embedded microfluidic device for capture, release and in situ manipulation of cancer cells. (June 2020) - Zhou, Lingfei; Zhang, Aihua; Mo, Jingshan; Xiu, Shengjie; Hang, Tian; Feng, Jianming; Wen, Rui; Liu, Di; Yang, Cheng; Feng, Yuping; Huang, Yan; Hu, Ning; et al.
Graphical abstract: The degradable porous nanoflower substrate (PNFS)-embedded microfluidic device could integrate multiple functionalities of effective CTC capture, in situ intracellular delivery, and nondestructive CTC release on a single device. This device promises to be a versatile and efficient platform for CTCs analysis, with great potential for the futuristic cell-based cancer diagnostics and therapies. Highlights: A degradable porous nanoflower substrate-embedded microfluidic device was developed. Multi-functions of effective CTC capture, in situ intracellular delivery and CTC release were integrated in a single device. Drugs were in-situ delivered into the captured cancer cells for modifications. The modified cells were nondestructive released from the same single device. The device provides a versatile and efficient platform for CTCs analysis. Abstract: Circulating tumor cell (CTC) detection has become a powerful tool for early diagnosis of metastasis and precise monitoring of cancer progression. While existing microchips have achieved promising progress on CTC capture, facile release and in situ regulation of CTC from devices for downstream analysis have rarely been realized. Herein, we demonstrated a porous nanoflower substrate (PNFS)-embedded microfluidic device that integrated multiple functionalities of effective CTC capture, in situ intracellular delivery, and nondestructive CTC release on a single device. The core of the device, PNFS, consisting of hierarchical Zn-phosphate composite structure on a nanoporous membrane, was produced by converting from micro/nano-fabricated ZnO nanostraws by low-temperature hydrothermal method and could be degraded via sodium citrate solution treatment for 20 min. Cancer cells could be captured on the PNFS with high efficiency up to 93.9 ± 1.7% after specific antibody conjugations, and be non-destructively released from the PNFS by using biocompatible sodium citrate to rapidly dissolve the PNFS at room temperature. In addition, the degradable PNFS was integrated with a microfluidic electroporation device, allowing in situ intracellular molecular delivery into the captured cells for cell modifications, where such reengineered cells could be further released for subsequent applications. This device promises to be a versatile and efficient platform for CTC analysis, with great potential for the futuristic cell-based cancer diagnostics and therapies.